Assessing tropical forest restoration after fire using birds as indicators: an Afrotropical case study - Rurangwa, ML; Matthews, TJ; Niyigaba, P; Tobias, JA; Whittaker, R (Elsevier, 2020)
The necessity to restore rainforest habitats degraded by anthropogenic fires is widely recognized, however, research on restoration approaches has mainly centred on the recovery of forest structural complexity. There is insufficient evidence on the efficacy of restoration methods in the recovery of the faunal diversity and features linked to key ecosystem functions. We assessed the taxonomic diversity and functional trait structure of bird assemblages in undisturbed primary forest and fire-affected habitats undergoing natural regeneration, as well as areas of assisted natural regeneration, in Nyungwe National Park, Rwanda. We compiled bird occurrence data from point-count sampling, and obtained morphological traits for all species in our assemblages using measurements taken from wild birds and museum specimens. We found marked differences in species composition between primary forest habitats and regenerating forest, with similarity increasing over time since perturbation. Taxonomic diversity was higher in primary forest, and similar between the two restoration approaches. Functional diversity was lower in assisted naturally regenerated habitats, although separate analyses within dietary guilds revealed no differences across habitats. Among desired restoration outcomes, tree species diversity was the leading positive driver of avian species diversity, fern coverage exerted negative effects, while canopy cover had a positive but weak influence. Our findings underscore the importance of preventing anthropogenic fires in tropical rainforest since their impacts on ecological processes are not easily reversed, as shown by the lack of improvement in avian diversity metrics under assisted naturally regeneration in relation to natural regeneration. We stress the need to document both floral and faunal recovery in order to aid informed decision-making on restoration methods.